1986
DOI: 10.1037/h0085640
|View full text |Cite
|
Sign up to set email alerts
|

The application of psychodidactic support groups to facilitate female offenders' adjustment to prison.

Abstract: A program designed to facilitate newly admitted female immates' adjustment to prison is outlined. The supportive and psychodidactic components of the program are described, and the use of inmate cofacilitators is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…There have also been studies on the relationship between female prisoners' participation in treatment programs and their prison adjustment. Those who participate in treatment intervention programs show better adjustment to the prison environment than female prisoners not involved in therapy (Negy, Woods, & Carlson, 1997;Sultan, Long, & Kiefer, 1986;Sultan, Long, Schrum, Selby, & Calhoun, 1985). Loper (2002) discovered that female prisoners convicted of drug possession offenses were more satisfied with the prison environment, experienced less internal distress, conflict, and mental illness, and took a more positive view toward imprisonment.…”
Section: Female Offenders' Prison Adjustmentmentioning
confidence: 99%
“…There have also been studies on the relationship between female prisoners' participation in treatment programs and their prison adjustment. Those who participate in treatment intervention programs show better adjustment to the prison environment than female prisoners not involved in therapy (Negy, Woods, & Carlson, 1997;Sultan, Long, & Kiefer, 1986;Sultan, Long, Schrum, Selby, & Calhoun, 1985). Loper (2002) discovered that female prisoners convicted of drug possession offenses were more satisfied with the prison environment, experienced less internal distress, conflict, and mental illness, and took a more positive view toward imprisonment.…”
Section: Female Offenders' Prison Adjustmentmentioning
confidence: 99%
“…Within prisons, support groups can provide essential emotional support to inmates. The possibility of sharing their experience with others in similar situations encourages detainees to confront their emotions, with a consequent reduction in the avoidance of their emotional state and a better acceptance of the imprisonment condition, which in turn positively affect their mental health (Sultan, Long, & Kiefer, 1986). Indeed, a large body of literature has shown that psychological well‐being is greatly affected by how individuals approach their inner states rather than how negative and intense such states are (Bond et al., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies were more issue oriented; the focus of the studies appeared to be the issue in question, not the population or sample used in the study. The issues explored included sexual victimization (Saxe & Johnson, 1999;Talbot et al, 1999;Threadcraft & Wilcoxon, 1993), divorce (Graff et al, 1986), chemical dependency (Gilbert & Beidler, 2001;Kauffman et al, 1995), self-esteem (Yahne & Long, 1988), leaderless groups (Kees, 1999), adjustment to prison (Sultan, Long, & Kiefer, 1986), dependency on others (Perkins & Lynch, 1992), career intervention (Mawson & Kahn, 1993), occupational engagement (Rebeiro & Cook, 1999), career choice (Peng, 2001), and posttraumatic stress disorder (PTSD; Schlee et al, 1998).…”
Section: From Which Specific Populations Were the Samples Drawn?mentioning
confidence: 99%
“…Half of the studies reported that their findings were helpful for women's groups; the other half reported that their findings were important but not in specific relation to women. Multiple studies reported an increase in women's feelings of support (Constantino et al, 2001;Jarrett et al, 2000;Kees, 1999;Lovenfosse & Viney, 1999;Sultan et al, 1986). Many studies also reported that the women's group increased the participants' self-esteem or self-concept (Perkins & Lynch, 1992;Yahne & Long, 1988) and self-efficacy (Sullivan & Mahalik, 2000).…”
Section: What Findings Were Reported In the Articles?mentioning
confidence: 99%